Active redox cycling of phosphorus on the early Earth - Jihua Hao; Xing Li; Pengcheng Ju; Matthew Pasek (Nature Communications)
Phosphorus is a critical bio-limiting nutrient in Earth’s ecosystems. A new study published in Nature Communications reports high availability of phosphite for possibly biological uptake in the late Archean ocean, suggesting an active redox cycling of phosphorus on the early Earth.